Pregnancy and health-related quality of life: A cross sectional study (Colombia Medica, 2011)
Objective: To evaluate and identify determinants of health related quality of life (HRQoL) during pregnancy. Methods: In this descriptive exploratory study in sixty-four nulliparous pregnant women, completed the questionnaire: HRQoL (Colombian standard version of the Medical Outcome Study Short-Form Health Survey -SF12v2-), and sociodemographic determinants (i.e., age, place of origin, education, marital status, and occupation) during the second trimester.Results: Mean age of patients included was 19.1±2.7 years old and gestational age was 17.6 ± 3.4 weeks. The participants reported higher HRQoL scores in the vitality domain (56±11), followed by mental health (5110), and general health (50±11).Moreover, the lowest score was demonstrated in the domains of emotional role (18±5) and physical role (25±4). Having a higher household socioeconomic level was significantly correlated with higher scores in the physical role, general health, social functioning, emotional role, and mental health. Being married or cohabiting was significantly correlated with all the SF-12v2 domains, with the exception of the Bodily pain domain.Conclusions: While we have included a comprehensive assessment of socioeconomic variables needed to assess and identify the factors determining the HRQoL during pregnancy, further studies are needed that can guide the expectations of women, their health care providers, and public policy.